Answer: f'(x) = - cos^2(sin(x^2))
Step-by-step explanation:
Derivative of:
f(x) = Sin^2(cos(x^2))
f'(x) = cos^2(-sin(x^2)
f'(x) = - cos^2(sin(x^2))
Answer:
This is what I got, the second one, the third one, and the fifth one.
Step-by-step explanation:
Answer:
x + 2y = 4
x − y = − 3
x − y =9 , x + y=6
x + y =4,
x− y =2
Step-by-step explanation:
The distance between two points can be calculated using the following formula:
distance = sqrt [ (x2-x1)^2 + (y2-y1)^2]
Now, we are given the two points (5,4) and (1,-2)
Substitute with the given points in the above equation to get the distance as follows:
distance = sqrt [(1-5)^2 + (-2-4)^2]
distance = sqrt [16+36] = sqrt[52]
distance = 2√13 = 7.2111 units